(untitled) (Journal of Hama University, 2019)
This study aimed to recognizing the effective of using (V) Map of Teaching Science on the achievement Of The Basic Fourth Grade Pupils, the study experimental method adopted to achieve objectives of the study were used achievement test consisting of 20 items, and the research sample consisting of (87) students, were divided into two groups: a control group (42) and the experimental group (45), and the most important results of theresearch: 1. There are differences statistically significant at the level of significance (0.05) between average degrees of the experimental group students and the average degrees of the control group students in the post- achievement test due to the learning method variable. 2. There are differences statistically significant at the level of significance (0.05) between the average degrees of the experimental group students in the post- achievement test due to gender variable (male / female), interaction between the teaching method and gender.